Propriedades antinociceptivas e antioxidantes do disseleneto de bis(fenilimidazoselenazolila) em roedores - Chagas, Pietro Maria (2016)
The current available drugs for treatment of disorders related to pain and inflammation present several adverse effects, then the investigation for novel molecules are required. It is known that organoselenium compounds have important properties antioxidant, anti-inflammatory and antinociceptive molecules. The objective of this thesis was to evaluate the antinociceptive and antioxidant properties of the bis(phenylimidazoselenazolyl) diselenide (BPIS) in rodent. In order to accomplish this objective, the compound was investigated in different experimental models and the results were divided in two research articles and two manuscripts. Firstly, the results of the 1st article demonstrate the antinociceptive property of BPIS in thermal and chemical nociceptive models, and it was also observed that the compound did not induce, in the tested doses, any behavioral change or apparent toxicity. In the 2nd article, the study was focused on the research of the antioxidant potential of the BPIS, and it was reported the in vitro antioxidant effect of the compound in front of models of lipid peroxidation and protein carbonylation induction in brain homogenates, in addition to free radical scavenger and antioxidant enzymes mimetic activity. In relation to the investigation of the in vitro toxicity, it was observed inhibitory effects on the activity of enzymes, such as δ-ALA-D and Na+, K+-ATPase, as well as [3H]glutamate uptake, however, these effects were detected in higher concentrations than that the compound presented antioxidant effect. In vivo, BPIS was also evaluated in front of the model of oxidative damage induced by sodium nitroprusside (SNP); presenting protective effect against the increase in lipid peroxidation and protein carbonyl levels, as well as the decrease in non-protein thiols induced by SNP. In the 1st manuscript, BPIS was evaluated in the inflammatory nociception induced by intraplantar injection of complete Freund’s adjuvant (CFA), where the mechanical allodynia induced by CFA was reversed by the compound; it was also seen that the BPIS effect was blocked by L-arginine pre-administration. In relation to the tissue analysis of the 1st manuscript, though BPIS did not protected against the changes induced by CFA in the paw tissue, it protected against the increase in the nitric oxide related species (NOx) in the spinal cord. Besides that, BPIS also reversed the augment in malondialdehyde levels and reduction in [3H]glutamate uptake induced by CFA in the spinal cord. In the 2nd manuscript, BPIS was evaluated in front of the type-II collagen-induced rheumatoid arthritis model (CIA), where it was effective in reversing the mechanical allodynia and thermal hyperalgesia induced by the model. In this protocol, BPIS decreased the paw myeloperoxidase activity, as well as the NOx levels in the spinal cord, that were altered by CIA. BPIS also blocked the increase in NFκB levels and induced a per se decrease in cyclooxygenase-II levels. Together, the results in this thesis suggest that BPIS is a molecule of interest to the development of novel therapies for the treatment of disorders related pain and inflammation, and that BPIS antinociceptive property is related to its antioxidant mechanism, mainly its interference on the nitric oxide pathway.